Studying The Spectrum Of Allergenic Sensitization Of The Population In The Regions Of The Republic Of Uzbekistan (Journal of Pharmaceutical Negative Results, 2023)
One of the most modern and effective methods for studying allergology is molecular allergological research. [1]. Thanks to this method, we have the opportunity to diagnose allergic diseases at the molecular level, make an accurate diagnosis, identify the main major molecule of the causal allergen, establish cross-censitization and conduct effective immunotherapy [1,2]. Very high therapeutic effectiveness of immunotherapy leads to a decrease in the incidence of allergic diseases [3].